Traditional medicinal plants used by hypertensive patients in Belize: a qualitative evaluation of beliefs and practices - Mphuthi, David D. (2023)
Belize is rich in rainforest and vast medicinal plants that have the potential for drug discoveries. Few studies have examined the use of medicinal plants in the management of chronic diseases in Belize. The present study appraised indigenous Belizeans' opinions, beliefs, and practices of medicinal plants used for hypertension management. Twenty-four hypertensive patients were interviewed using a semi-structured interview guide from January to May 2019. Interview results were transcribed using Microsoft Excel and loaded into qualitative data analysis (QDA) Miner Lite version 2.0.6 online software for coding. The integrated themes and sub-themes generated were presented in narrative passages and used to summarize study findings on medicinal plants used in the management of hypertension in Belize.